Work-Family Conflicts Among Married Professional Women in The Construction Industry - Yeo, Jing Yi; Seow, Ta Wee; Mohamed, Sulzakimin; Goh, Kai Chen (Research in Management of Technology and Business, 2022)
Work-family conflict (WFC) has become a popular issue in modern life. Most of the individuals experience interpersonal and intrapersonal conflicts and try to balance these conflicts between work and family. The women entering the workplace is a serious problem that causes work-family conflict and this has affected work and family relationships. The objectives of this research are to identify the factors of work-family conflict among married professional women in the construction industry and to study the way to reduce work-family conflict among married professional women in the construction industry. Scope of this research is focused on work-family conflict among married professional women in the construction industry of Johor. The quantitative method was used in this research where a questionnaire survey was distributed to marriage professional women who are working in the construction industry Johor area, Malaysia. There were 371 married professional women in Johor were the respondents for this research and after the data collection there were 238 (64.15%) questionnaires were received back for this research. The data were analysed using SPSS software for analysed on descriptive statistic to obtain the result. After obtaining the data, the first objective is achieved by determining the factor of excessive of workload, job stress and work from home (WFH) is the factor that causing work-family conflict among married professional women in the construction industry. The second objective is achieved by determining the way of support from family members is the way to reduce work-family conflict among married professional women in the construction industry. In conclusion, this study is beneficial to the marriage professional women and construction companies more understanding about the factors that cause work-family conflicts and emphasize ways in reduce work-family conflict in the construction industry.